KEPEMIMPINAN PEREMPUAN DALAM IBADAH: TAFSIR TRANSFORMATIF ATAS DISKURSUS IMAM PEREMPUAN BAGI LAKI-LAKI DALAM SHALAT - Elya Munfarida (Yinyang: Jurnal Studi Islam, Gender dan Anak, 2015)
Controversy about women ability as imam for men, have become polemic of past ulama. Four imam mazhab firmly refuse women imamah to men. Ulama discourse about womenâ€™s imamah reflects their inclination to patriarchal interest. It is clear from the existence of rational inconsistency on their thought: in one side on imam general prerequisite, religious understanding and al-Qurâ€™an fluently as main criteria. However, on the other side, when discussing about women imamah, those substantial criteria neglected. Their refusal did not based on consideration whether women comply with qualification that being prerequisite, but simple because on â€œbecause she is womanâ€. Meanwhile, Abu Tsaur, al-Thabari, and Mazini as ulama side whom absolute permit women as imam. However, their view did not emerge to surface; moreover almost disappear from Islamic thought discourse. On this point, the appointment of Ummu Waraqah as imam for men can be understood as implementation and affirmation of human equality idea, which existed on tauhid doctrine. Therefore, men and women have chance to become imam, as long as comply with qualification prerequisite.